2004
DOI: 10.1021/ie034239a
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Molecular Characterization Approach for the Simulation of FCC Feedstocks

Abstract: Feedstock quality affects the fluid catalytic cracking (FCC) process to such an extent that even the operating variables or the catalyst selection seem to be of secondary importance. This paper focuses on the way that the bulk properties of an FCC feedstock can explain the extent of catalytic reactions (crackability) and coke production (coking tendency). The final goal of this effort is to develop a model for the characterization of fluid catalytic cracking feedstocks on the basis of standard analytical proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 24 publications
2
53
0
Order By: Relevance
“…This was attributed to the high aromatic contents in the feeds containing LCO .The study has found an optimum content of LCO in the FCC was to be 7 vol % ,which maximizes both gasoline production and gasoline RON. [5] in their research studies on bulk molecular characterization approach for the simulation of FCC feedstocks. In their study they had presented a bulk molecular characterization approach for the simulation of FCC feedstock regarding their relative potential to enhance catalytic cracking and coke formation .The final models for the prediction of crackability and coking tendency incorporated the specific gravity, the refractive index, and the TBP distillation of the feedstocks, along with the sulfur ,nitrogen, and carbon contents.…”
Section: Initial Components In Feedmentioning
confidence: 99%
“…This was attributed to the high aromatic contents in the feeds containing LCO .The study has found an optimum content of LCO in the FCC was to be 7 vol % ,which maximizes both gasoline production and gasoline RON. [5] in their research studies on bulk molecular characterization approach for the simulation of FCC feedstocks. In their study they had presented a bulk molecular characterization approach for the simulation of FCC feedstock regarding their relative potential to enhance catalytic cracking and coke formation .The final models for the prediction of crackability and coking tendency incorporated the specific gravity, the refractive index, and the TBP distillation of the feedstocks, along with the sulfur ,nitrogen, and carbon contents.…”
Section: Initial Components In Feedmentioning
confidence: 99%
“…The pseudo-steady state and dynamic sub-models that constitute the dynamic simulator, as developed in CPERI, have been presented in the literature (Bollas et al, 2002;Bollas et al, 2004;Faltsi-Saravelou, Vasalos & Dimogiorgas, 1991) and will be briefly adduced in this section. A kinetic-hydrodynamic model was developed for the simulation of the pilot riser reactor in pseudo-steady state conditions (Bollas et al, 2002).…”
Section: Model Descriptionmentioning
confidence: 99%
“…The prediction of gas-oil conversion and coke yield are the only two lumps of the riser sub-model, essential for inclusion in the complete simulator, which reduces the necessity of using a more detailed lumped model. The effect of feedstock properties on gas-oil conversion and coke yield was expressed through semi-empirical correlations developed on the basis of experiments performed with constant catalyst and a variety of feedstocks (Bollas et al, 2004). The effect of catalyst type was expressed through a "catalyst index" (Bollas et al, 2004).…”
Section: Model Descriptionmentioning
confidence: 99%
See 2 more Smart Citations